How the use of creatine supplements can elevate serum creatinine in the absence of underlying kidney pathology. (19th September 2014) - Williamson, Lydia; New, David
Abstract : Serum creatinine is a widely used marker in the assessment of renal function. Elevated creatinine levels suggest kidney dysfunction, prompting the need for further investigation. This report describes a case in which the consumption of the bodybuilding supplement creatine ethyl ester resulted in raised serum creatinine in the absence of true underlying kidney pathology. The abnormalities reversed after discontinuation of the supplement. A case of pseudo renal failure was recognised and kidney function was concluded to be normal. This report aims to address the mechanisms by which the ingestion of creatine ethyl ester can mimic the blood results expected in advanced renal failure, and confronts the problems faced when relying on serum creatinine as a diagnostic tool.